Philippine medical thesaurus on anatomy animal structures, sense organs and food beverages in Pangasinan - Franco, Harold T. 1982-
The incorporation of switching language in the construction of Philippine Medical Thesaurus has made all the information contained in the Philippine Medical thesaurus accessible to people of different country and languages. Although thesaurus serve as a great tool for information storage, management and retrieval, the inclusion of the switching language like conversion of all the terms in the thesaurus from one language to another like that of Pangasinan could create a lot of problem. With this idea, how could the Philippine Medical Thesaurus in Anatomy : Animal Structures, Sense Organs and Food and Beverages in Pangasinan be beneficial and can cater to the information needs of its end-users? Being a succeeding work in Philippine Medical Thesaurus, it delivers the problem with the resolution of constructing a thesaurus of carefully defined terms and terms that are properly examined to assure the end-users that the terms are of good source of information. During the study, different problems have kept arise but various solutions to these problems are carried out in order to resolve such.